City sense : shaping our environment with real-time data - Capelli, Lucas (New York : Actar, 2013)
This publication compiles the winning and the finalist entries of the City Sense competition, organized by the Institute of Advanced Architecture. The competition was open to architects, engineers, planners, designers and artists who wanted to contribute to progress in making the world more habitable by developing proposals capable of responding to emerging challenges in areas such as ecology, information technology, architecture, and urban planning, with the purpose of balancing the possible impact of real-time data collection on sensor-driven cities. The competition jury, which was composed of architects, experts from a wide range of fields and directors of some of the world s foremost architecture schools, were looking for outstanding proposals of any scale, for any city in the world. The book presents a selection of the best projects on Smart Cities, Eco Neighbourhoods, Self-Sufficient Buildings, Intelligent Homes and other proposals which examine the phenomena of sensor-driven cities and intelligent behaviouralsystems.
Keywords: Civic art